2023
DOI: 10.1007/s40615-023-01588-4
|View full text |Cite
|
Sign up to set email alerts
|

Telehealth for Chronic Disease Management Among Vulnerable Populations

Abstract: Chronic diseases disproportionately affect patients in low-income minority groups who traditionally use in-person healthcare services. COVID-19 disrupted their routines and limited options for people to receive care; this could exacerbate health inequities. The study examined telehealth chronic disease management among low-income minority groups. We used Florida Medicaid claims data from March to December 2020 and the American Consumer Survey to examine the study objectives. Data were analyzed using Linear and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…Furthermore, there remains an inequity in access to care in telemedicine for vulnerable population, such as older people. A strategy to promote electronic health education and provide the necessary equipment to ensure telemedicine equity is needed [ 61 ]. Therefore, the use of telemedicine should be tailored depending on the setting and needs of the population and health system.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, there remains an inequity in access to care in telemedicine for vulnerable population, such as older people. A strategy to promote electronic health education and provide the necessary equipment to ensure telemedicine equity is needed [ 61 ]. Therefore, the use of telemedicine should be tailored depending on the setting and needs of the population and health system.…”
Section: Discussionmentioning
confidence: 99%
“…Health inequities are delineated by race, ethnicities, geographic regions, socioeconomic status, and other social determinants of health. Inequities in access have considerable influence on quality of life and related outcomes (Williams & Shang, 2023). Disparities in access to telemedicine care today can easily exacerbate the preexisting challenges in providing primary care and chronic disease management for vulnerable populations.…”
Section: Health Inequalities and Digital Healthcarementioning
confidence: 99%
“…18 In this regard, a study by Nohra et al in 2020 demonstrated the feasibility and efficiency of a self-care program through telehealth (remote health) for patients with moderate to severe COPD 19 through facilitation of patient monitoring, treatment, and education. 20 The self-care method combined with readily accessible mobile technology increases the patients' responsibility toward themselves and helps them change high-risk behaviors. 21 In 2018, the WHO recommended the use of mobile phone applications and telemedicine to improve treatment and care outcomes in patients with COPD.…”
Section: Introductionmentioning
confidence: 99%